Do We Need Extensor Retinacular Enhancement on Broström Lateral Ankle Repair? A Systematic Review and Meta-analysis - Butarbutar, John; Irvan, Irvan; Lim, Michael Anthonius; Pranata, Raymond (Open Access Macedonian Journal of Medical Sciences, 2021)
Aims This meta-analysis compared inferior extensor retinaculum (IER) enhancement in Broström-Gould procedure and anatomical Broström repair. We aim to evaluate functional ankle score (American Orthopaedic Foot & Ankle Society (AOFAS) score, Karlsson score), talar tilt, talar anterior translation, and complications between both groups. Methods A comprehensive systematic literature search was carried out using Wiley Library, Scopus, Pubmed, ScienceDirect, and EuropePMC databases from inception up until 19 December 2020. While the intervention was IER enhancement, the control was those without IER enhancement. The primary outcome was the functional ankle score (AOFAS and Karlsson score). The secondary outcomes were talar tilt, talar anterior translation, and other complications. Results There was a total of 298 patients from 7 studies included in this systematic review and meta-analysis. IER enhancement was associated with lower AOFAS (mean difference -1.115 [-2.197, -0.033], p=0.043; I2: 0%) during follow-up. Lower Karlsson score was observed in the IER enhancement group (mean difference -2.004 [-3.442, -0.567], p=0.006; I2: 3.71%) during follow-up. Talar tilt (mean difference -0.145 degree [-0.436, 0.146], p=0.329; I2: 0%) and anterior displacement (mean difference -0.109 mm [-0.096, 0.314], p=0.299; I2: 0%) in the two groups were similar on follow-up. The complications were similar in both groups (OR 0.87 [0.40, 1.89], p=0.719; I2: 0%). Meta-regression analysis indicates that the association between IER and AOFAS was not affected by age (p=0.927) and male gender (p=0.930). Conclusion This meta-analysis showed that ATFL repair with non-IER enhancement was non-inferior compared to those with IER enhancement.